Oil deterioration prevention material and fryer using the same

By using an oil anticorrosion material containing specific metal oxides, the problem of oxidation and aging of oil during the decoction process is solved, and the long-term anti-corrosion and efficient greasiness of oil are achieved, reducing the operating costs of the enterprise and improving the quality of food.

JP2025037286APending Publication Date: 2025-03-18PROTEAN K CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023144095
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-06
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

Oil is prone to oxidation and aging during the frying process, resulting in a decrease in the quality of the oil, affecting the taste and health and safety of the food. At the same time, the replacement and treatment of oil increase the cost of the enterprise.

Method used

An oil-preserved material containing elements such as iron, sulfonium, magnesium, aluminum, titanium and zirconium is used. The material is measured by X-ray fluorescence analysis, including 30-40% iron oxide, 15-25% sulfonium oxide, 5-15% magnesium oxide, 4-8% aluminum oxide, 3-7% titanium oxide and 1-2% zirconium oxide to form a material that can effectively disperse and prevent oxidation in the oil.

Benefits of technology

This material can effectively prevent the oxidation and aging of oil, reduce the viscosity of oil, maintain the fluidity and quality of oil, thereby reducing the frequency of oil replacement, reducing the operating costs of enterprises, and improving the taste and texture of fried foods.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025037286000001_ABST
    Figure 2025037286000001_ABST
Patent Text Reader

Abstract

To provide an oil deterioration prevention material capable of suppressing deterioration of oil used to fry food materials, and fryer using the oil deterioration prevention material.SOLUTION: An oil deterioration prevention material (1), when elements contained therein are measured as metals or oxides by X-ray fluorescence analysis, contains 30-40 mass% of ferric oxide (Fe2O3), 15-25 mass% of thorium oxide (ThO2), 5-15 mass% of magnesium oxide (MgO), 4-8 mass% of aluminum oxide (Al2O3), 3-7 mass% of titanium oxide (TiO2), and 1-2 mass% of zirconium oxide (ZrO2: zirconia).SELECTED DRAWING: Figure 3
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an oil deterioration prevention material capable of preventing deterioration of oil during cooking (frying) of food ingredients in oil, and a fryer for frying food ingredients in oil, which uses the oil deterioration prevention material. [Background technology]

[0002] Fryers can be broadly categorized into the following two types. The first type is a type that continuously puts food ingredients into an oil vat and continuously discharges the fried food ingredients (see, for example, Patent Document 1). The second type is a type that immerses a frying basket containing the food ingredients to be fried in the oil vat together with the food ingredients, and removes the frying basket from the oil vat once the food ingredients have been fried (see, for example, Patent Document 2). The first type is often used in large facilities such as food processing plants, while the second type is often seen in convenience stores and so-called "fast food" retail outlets.

[0003] Regardless of the type, there is a problem that the oil deteriorates when food is fried. Food fried in deteriorated oil not only loses flavor and taste, but also has the risk of adversely affecting the health of users who consume the food. Therefore, when the oil used in a fryer deteriorates, the deteriorated oil is discarded and new, undeteriorated oil is supplied to the fryer. However, due to the current social situation, the unit price of oil has risen sharply, and the cost of disposing of deteriorated oil and supplying new oil to fryers has also skyrocketed, causing serious problems for businesses that use fryers.

[0004] The most direct solution to this problem is to suppress the deterioration of oil, but the deterioration of oil caused by frying food in a fryer is an unavoidable phenomenon, and no effective solution to the above problem has yet been proposed. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2005-296417 A [Patent Document 2] Special Publication No. 49-16623 Summary of the Invention [Problem to be solved by the invention]

[0006] The present invention has been proposed in consideration of the problems of the prior art described above, and aims to provide an oil deterioration prevention material that can suppress the deterioration of oil even when frying food ingredients, and a fryer that uses the oil deterioration prevention material. [Means for solving the problem]

[0007] In the course of continuing research into improving fryers, the inventors discovered that by placing a mixture having a specific composition in an oil tank, deterioration of the oil can be suppressed. The oil deterioration prevention material (1) of the present invention has been proposed based on such findings, Contains iron, thorium, magnesium, aluminum, titanium, zirconium, When the elements contained are measured as metals or oxides by X-ray fluorescence analysis, Iron oxide (Fe2O3) 30 to 40 mass% Thorium oxide (ThO2) 15 to 25 mass% Magnesium oxide (MgO) 5 to 15 mass %, Aluminum oxide (Al2O3) 4 to 8 mass%, Titanium oxide (TiO2) 3 to 7 mass% 1 to 2 mass% of zirconium oxide (ZrO2: zirconia), It is characterized by inclusion.

[0008] The oil deterioration prevention material (1) of the present invention is Contains manganese, niobium, uranium, calcium, lead, phosphorus, hafnium, rubidium, tin, copper, and gallium. When the elements contained are measured as metals or oxides by X-ray fluorescence analysis, It is preferable that the material contains 0 to 1.0 mass% of each of manganese oxide (MnO), niobium pentoxide (Nb2O5), triuranium octoxide (U3O8), calcium oxide (CaO), lead monoxide (PbO), diphosphorus pentoxide (P2O5), hafnium oxide (HfO2), rubidium oxide (Rb2O), copper oxide (CuO), and gallium oxide (Ga2O3). In other words, the oil deterioration prevention material (1) of the present invention is, When the elements contained are measured as metals or oxides by X-ray fluorescence analysis, It is preferable that the material does not contain any of the following, or contains only 1.0 mass% or less: manganese oxide (MnO), niobium pentoxide (Nb2O5), triuranium octoxide (U3O8), calcium oxide (CaO), lead monoxide (PbO), diphosphorus pentoxide (P2O5), hafnium oxide (HfO2), rubidium oxide (Rb2O), copper oxide (CuO), or gallium oxide (Ga2O3).

[0009] The fryer (10-1) of the present invention is The oil deterioration prevention material (1: any one of the oil deterioration prevention materials according to claims 1 and 2) is sintered to form a sintered body (1A) which is disposed in an oil tank (2). Here, the sintered body (1A) is formed into a spherical shape, and the spherical sintered body (1A) is placed in the internal space of a hollow body (3) made of a material (e.g., a mesh-like member or a punched metal) having a large number of openings (3A), and it is preferable that the hollow body (3) having the sintered body (1A) placed in the internal space can be immersed in an oil tank (2).

[0010] The flyer (10-2) of the present invention is The oil deterioration prevention material (1: any one of the oil deterioration prevention materials of claims 1 and 2) is sprayed onto a metal plate (4) to cover the surface layer of the metal plate (1B: a metal plate having a surface layer covered with the oil deterioration prevention material 1), and the metal plate is placed in an oil tank (2). Here, the method of thermally spraying the oil deterioration prevention material (1) of the present invention (on an object to be thermally sprayed: for example, a metal plate 4) is as follows: The oil deterioration prevention material (1: the oil deterioration prevention material according to any one of claims 1 and 2) is heated to a melted or semi-melted state, The oil deterioration prevention material (1) in a molten or semi-molten state is sprayed onto an object to be thermally sprayed (e.g., a metal plate 4) and allowed to collide with the surface layer of the metal plate; The oil deterioration prevention material (1) is laminated and attached to the surface layer of the metal plate (to create a metal plate 1B whose surface layer is covered with the oil deterioration prevention material 1). In addition, the frying pan of the present invention is characterized in that the surface of the body (at least the surface that comes into contact with food) is coated with the oil deterioration prevention material described above (the oil deterioration prevention material of either claim 1 or 2), and is further coated with a fluororesin (fluorocarbon resin). Here, the fluororesin (fluorocarbon resin) can be, for example, tetrafluoroethylene (Teflon (registered trademark): PTFE). Effect of the Invention

[0011] The molecules of oils, including edible oils, are attracted to each other by intermolecular forces (van der Waals forces) to maintain a chemically stable state. Oil used for frying food oxidizes and ages rapidly when heated, contaminated with impurities, or comes into contact with metal. Oil used for deep frying (frying oil) contains all the conditions for rapid oxidation. In addition to changing color and emitting an odor, oxidized oil also increases in viscosity as it breaks into large, clumpy molecules. According to the inventor's research, the oil deterioration prevention material (1) of the present invention has the ability to disperse these clumped molecules, and the surface tension of the dispersed oil molecules decreases, resulting in an increased disorder. In other words, the oil deterioration prevention material (1) of the present invention acts on the molecules of a fluid containing oil by ions and other forces, and disperses the molecules of the fluid. The dispersed (disintegrated) molecules move around individually, increasing their degree of freedom, which reduces the viscosity of the oil and allows it to maintain a non-sticky (so-called smooth) state. As a result, by using the oil deterioration prevention material (1) of the present invention, the oil in fried foods can be easily removed, and the adhesion of viscous oil to the surface of fried foods can be prevented, improving the texture.

[0012] Here, the oil deterioration prevention material (1) of the present invention contains a radioactive substance, and due to minute radiation from the substance, the oil molecules that have deteriorated and become clumpy due to multiple molecules attracting each other, are dispersed (broken apart) and become non-viscous, so that the oil molecules can move around individually and their degree of freedom is increased. At the same time, it is presumed that negative ions are supplied from the oil deterioration prevention material (1) of the present invention (for example, if installed in an oil tank 2, to the oil in the oil tank 2), and the oxidation (deterioration) of the oil is suppressed by the reducing action of the negative ions. Alternatively, the oil deterioration prevention material of the present invention contains a material (excitation material) containing the radioactive substance, and by having the above-mentioned composition, forms a crystal structure as a spontaneously polarized polar material. Therefore, it is presumed that radiation from the radioactive substance causes a disturbance in the electric field of the spontaneously polarized crystal particles, generating negative ions. According to the inventor's research, the amount of negative ions generated by the oil deterioration prevention material (1) of the present invention is 1000 ions / cm 3 ~10000 pieces / cm 3 The amount of radiation corresponding to this amount of negative ions is extremely low, about the same as that of radium hot springs, and does not have any adverse effects on the human body. In addition, the oil deterioration prevention material (1) of the present invention does not require an external power supply to suppress the oxidation of oil. With the oil deterioration prevention material (1) of the present invention, even without an external power supply, negative ions can continue to act on oil molecules that have deteriorated and become clumped together due to the attraction of multiple molecules to each other, until the excitation material no longer generates radiation. Furthermore, the oil deterioration prevention material (1) of the present invention is made of metals and inorganic materials, and therefore has excellent weather resistance, heat resistance, and corrosion resistance compared to materials that contain organic materials such as rubber and resin, and can be used semi-permanently.

[0013] According to the fryers (10-1, 10-2) of the present invention, the above-mentioned action and effect of the oil deterioration prevention material (1) of the present invention can be achieved by placing a sintered body (1A) obtained by sintering the above-mentioned oil deterioration prevention material (1: any of the oil deterioration prevention material of claims 1 and 2) in the oil tank (2), or by placing a metal plate (4) (1B: a metal plate whose surface layer is covered with the oil deterioration prevention material 1) having the above-mentioned oil deterioration prevention material (1: any of the oil deterioration prevention material of claims 1 and 2) sprayed onto the metal plate (4) to cover the surface layer in the oil tank (2). According to the fryers (10-1, 10-2) of the present invention, the sintered body (1A) or the metal plate (1B) only needs to be placed in the oil tank (2), so that the shape can be freely designed according to the size of the oil tank (2) of the fryers (10-1, 10-2). Furthermore, the oil deterioration prevention material (1: any of the oil deterioration prevention materials of claims 1 and 2) used in the fryers (10-1, 10-2) of the present invention can exert the effect of preventing oil deterioration without supplying electric power from outside, so that it can be freely installed regardless of the conditions of the installation location (position of the power outlet, etc.) as long as there is enough space to install the fryer.

[0014] In the fryer (10-1) of the present invention, a sintered body (1A) obtained by sintering the oil deterioration prevention material (1: any one of the oil deterioration prevention materials of claims 1 and 2) is placed in an oil tank (2), the sintered body (1A) is formed into a spherical shape, the sintered body (1A) formed into a spherical shape is placed in the internal space of a hollow body (3) made of a material having a large number of openings (e.g., a mesh-like member or a punched metal), and the hollow body (3) having the sintered body (1A) placed in its internal space is placed in the oil tank (2), thereby making it possible to keep the manufacturing cost low.

[0015] The method of spraying the oil deterioration prevention material (1) of the present invention (on a spraying target: for example, a metal base material 4) involves heating the oil deterioration prevention material (1) to melt or semi-molten state, spraying the oil deterioration prevention material (1) in a melted or semi-molten state onto the target to be sprayed (for example, a metal plate 4), colliding with the surface layer of the metal plate, and laminating and adhering the oil deterioration prevention material (1) to the surface layer of the metal plate (to create a metal plate 1B whose surface layer is covered with the oil deterioration prevention material 1). Therefore, the oil deterioration prevention material (1) of the present invention, which is an inorganic powder, is sprayed in a molten or semi-molten state (close to being molten) onto a base material including a thin plate of metal (materials usable in the food industry such as SUS and aluminum), and a laminated coating layer (coating) of a desired thickness can be formed on the metal base plate, and a film can be formed in units of, for example, 20 μm. By forming such a thin film (20 μm units), it becomes possible to suitably and easily control the deterioration suppressing and preventing action of the oil deterioration preventive material (1) of the present invention. In addition, the oil deterioration prevention material (1) of the present invention can be sprayed in a molten state or a semi-molten state (close to being molten) and thermally sprayed. 2It is possible to coat an area of ​​about 100 mm, and even when an oil deterioration prevention effect is required over a wide range (area), the oil deterioration prevention material (1) can be reliably coated on the surface layer of the metal base material (4). Alternatively, since the oil deterioration prevention material (1) of the present invention can be reliably coated on a desired area of ​​the surface layer of the metal base material (4), it is possible to manufacture a plurality of metal base materials of the same size coated with the oil deterioration prevention material (1) (1B: metal base material whose surface layer is coated with the oil deterioration prevention material 1) and arrange the plurality of metal base materials (1B) in an oil tank in an order, or to lay out the metal base materials of the same size coated with the oil deterioration prevention material (1) of the present invention in a bathtub, thereby fully exerting the oil deterioration prevention effect. In addition, if the oil deterioration prevention material (1) of the present invention is sprayed onto the metal plate (4), it can be molded into a desired size, so it can be installed in a narrow gap, etc. Therefore, there are few restrictions on the installation location.

[0016] Furthermore, if the oil deterioration prevention material (1) of the present invention is processed in advance into a near-net shape, it can be molded into any shape. In addition, the oil deterioration prevention material (1) of the present invention can be sprayed in a nearly molten state, so there is no elution or dust, opening up applications in the food industry, which is sensitive to the inclusion of impurities. In addition, the surface of the frying pan of the present invention (at least the surface that comes into contact with food) is coated with the above-mentioned oil deterioration prevention material (the oil deterioration prevention material of either claim 1 or 2), and is further coated with a fluororesin (fluorocarbon resin). Therefore, the inventors' experiments have confirmed that when food is cooked using various cooking methods that use oil, the texture of the cooked food, especially food that is fried in oil, baked in oil, or stir-fried, is extremely good. As mentioned above, this is presumably due to the action of the oil deterioration inhibitor. [Brief description of the drawings]

[0017] [Figure 1] FIG. 1 is an explanatory diagram showing an overview of a fryer in which food materials are continuously transferred downstream. [Diagram 2]FIG. 1 is an explanatory diagram showing an overview of a type of fryer that fries ingredients in a batch manner. [Diagram 3] 1 is a graph showing a comparison result of oxidation value (AV value) with and without the addition of an oil deterioration prevention material in Experimental Example 1. [Figure 4] FIG. 2 is an explanatory diagram showing an example of a sintered body obtained by sintering the oil deterioration prevention material in the first embodiment. [Diagram 5] FIG. 11 is an explanatory diagram showing a metal plate having an oil-deterioration prevention material laminated on a surface layer thereof by spraying the oil-deterioration prevention material onto the metal plate in the second embodiment. [Figure 6] FIG. 11 is an explanatory view showing a mode in which an oil deterioration prevention material is thermally sprayed onto a metal plate in the second embodiment. [Figure 7] FIG. 2 is an explanatory diagram showing the cross-sectional structure of a frying pan and its body according to the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] Hereinafter, an embodiment of the present invention will be described. 1 and 2 show a fryer using an oil deterioration prevention material 1 according to the present invention. Here, fryers are broadly classified into two types: one as shown in Figure 1, in which food ingredients are continuously put into an oil tank and the fried food is continuously discharged (fryer 10A), and one as shown in Figure 2, in which a frying basket containing the food to be fried is immersed in the oil tank together with the food ingredients and the frying basket is removed from the tank when the food ingredients are fried (fryer 10B). In the type of fryer 10A shown in Figure 1, during the cooking process of frying food ingredients 11A in oil, the food ingredients 11A are brought in from the entrance side 13 and continuously transported through the oil tank 2 to the exit side 17 by a paddling conveyor 15 and a transport conveyor 16 provided in the oil tank 2. In the illustrated embodiment, with regard to the form in which the oil deterioration prevention material 1 is arranged inside the fryer, a fryer in which a sintered body 1A of the oil deterioration prevention material 1 (for example) sintered into a spherical shape is arranged inside the oil tank 2 is shown with the symbol 10-1, and a fryer in which a metal plate 1B having the oil deterioration prevention material 1 sprayed on and coated on the surface with the oil deterioration prevention material 1 is arranged inside the oil tank 2 is shown with the symbol 10-2. However, for the fryers 10A and 10B shown in Fig. 1 and Fig. 2, which are drawings of the fryers, the oil deterioration prevention material can be arranged either as a sintered body 1A or as a metal plate 1B. Therefore, the reference numerals 10-1 and 10-2 are not used in Fig. 1 and Fig. 2.

[0019] In Figure 1, fryer 10A is equipped with an oil vat 2 that contains oil 12, a transport conveyor 14 at the entrance side 13 (upstream side) of the oil vat 2, a paddling conveyor 15 and a belt-type transport conveyor 16 that transport food ingredients 11A to the downstream side within the oil vat 2, and an output conveyor 18 that transports fried food 11B to the exit side 17 (downstream side) of the oil vat 2. Food ingredients 11A to be cooked (fried) (for example, sliced ​​potatoes, which are ingredients for potato chips) are fried in oil 12 in the oil vat 2. A transfer conveyor 14 transfers food ingredients 11A into the oil vat 2 at the inlet side 13 (upstream side) of the oil vat 2. The food ingredients 11A that have been brought into the oil vat 2 and are being fried are transferred to the downstream side of the oil vat 2 by a paddling conveyor 15 and a belt-type transfer conveyor 16. An output conveyor 18 transfers the fried food 11B to the outlet side 17 (downstream side) of the oil vat 2. The fried food 11B is carried away by a finished product transport conveyor 19. The level of the oil 12 in the oil vat 2 is adjusted within a predetermined range by a control device (not shown), and the temperature of the oil 12 is also adjusted within a predetermined range by a control device (not shown) according to the type of food material 11A. Above the oil vat 2 are placed a hood 20 that covers the entire oil vat 2, and a stack 21 for absorbing water vapor, oily smoke, etc. that are generated during frying. The paddling conveyor 15 has a function of spreading out the food ingredients 11A, which are fried while floating on the oil surface, in the oil 12 so that the food ingredients do not overlap each other, and also has a function of moving the food ingredients 11A downstream. A belt-type transport conveyor 16 is arranged downstream of the paddling conveyor 15. The conveyor belt 16A of the belt-type transport conveyor 16 is arranged so that the conveyor transport section below the oil level moves from the upstream side to the downstream side, and has the function of positioning the food material 11A below the oil level and immersing it in the oil 12, and allowing the entire food material 11A to move evenly through the oil 12 and be fried evenly.

[0020] In fryer 10A in Fig. 1, food materials 11A are continuously carried into oil vat 2 from inlet side 13 by transport conveyor 14, and while being fried in the oil in oil vat 2, they are transported from upstream to downstream in oil vat 2 by paddling conveyor 15 and belt-type transport conveyor 16, during which they are deep-fried in oil 12. Fried food materials 11B are continuously carried out to outlet side 17 of oil vat 2 by discharge conveyor 18. An oil deterioration prevention material 1 according to the embodiment is placed in the oil in the oil tank 2 of the fryer 10A. As described later, the oil deterioration prevention material 1 is a mixture containing a predetermined composition in a specific composition, and when placed in the fryer 10, the oil deterioration prevention material 1 is placed, for example, as a spherical sintered body 1A. Alternatively, the oil deterioration prevention material 1 is sprayed to create a metal plate 1B whose surface layer is covered with the oil deterioration prevention material 1, and such a metal plate 1B is placed in the oil tank 2. The oil deterioration prevention material 1 (1A or 1B) is not shown in FIG. 1.

[0021] FIG. 2 shows a type of fryer 10B in which food ingredients 11A to be fried are loaded into a basket 22, which is then immersed in heated oil 12 in an oil tank 2 to fry the food ingredients 11A in a batchwise manner. 2, fryer 10B includes a casing 23, an oil tank 2 that contains oil 12 for frying food material 11A to be cooked (fried), and a mesh-structured basket 22 that is disposed within oil tank 2 and that holds food material 11A during cooking. Oil tank 2 is disposed within casing 23 of fryer 10B. Basket 22 is attached to support member 24, which is configured to be able to be raised and lowered in the vertical direction (the direction of arrow A) by lifting device 25. Therefore, with basket 22 raised to a position above oil vat 2, food ingredients 11A are placed into basket 22, and basket 22 with food ingredients 11A placed therein is lowered to immerse food ingredients 11A in oil vat 2, whereby food ingredients 11A can be cooked (fried). An opening on the top surface of the oil vat 2 is provided with a lid 26, which is used to open and close the opening. When food ingredients 11A are placed in the basket 22 before cooking, the basket 22 is raised above the oil vat 2 and the lid 26 is opened. When the basket 22 containing the food ingredients 11A is immersed in the oil 12 in the oil vat 2 for cooking, the lid 26 is closed. FIG. 2 shows the state in which the basket 22 is immersed in the oil 12 for cooking, with the lid 26 closed. However, there are also cases in which the lid 26 is left open when the basket 22 is immersed in the oil 12 for cooking. The oil level of the oil 12 in the oil tank 2 is adjusted within a predetermined range by a control device not shown, and the temperature of the oil 12 is also adjusted within a predetermined range by a control device not shown according to the type of food material 11A.

[0022] In the fryer 10B of Fig. 2, as described above, a predetermined amount of food ingredients 11A is placed in the basket 22 which has been raised to a position above the oil vat 2 by the lifting device 25, and then the basket 22 is lowered to immerse the ingredients in the oil 12 and cook (fry) the ingredients 11A. Once the ingredients 11A have been cooked and fried, the basket 22 is raised to a position above the oil vat 2 and the cooked ingredients 11A are removed from the basket 22. By repeating this operation, the ingredients 11A are cooked in batches. Here, oil deterioration prevention material 1 according to the embodiment is placed in oil in oil tank 2 of fryer 10B, similarly to the case of fryer 10A in Fig. 1. As described in Fig. 1, oil deterioration prevention material 1 is a mixture containing a predetermined composition, and sintered body 1A obtained by sintering oil deterioration prevention material 1 into, for example, a spherical shape, or metal plate 1B having a surface layer covered with oil deterioration prevention material 1 by thermal spraying, is placed in oil tank 2. However, illustration of oil deterioration prevention materials 1 (1A, 1B) is omitted in Fig. 2.

[0023] As described above, the oil deterioration prevention material 1 according to the embodiment is disposed in the oil tank 2 of the fryers 10A and 10B shown in Figs. The oil deterioration prevention material 1 according to the embodiment contains iron (Fe), thorium (Th), magnesium (Mg), aluminum (Al), titanium (Ti), and zirconium (Zr). The content of each element is measured as a metal or oxide by X-ray fluorescence analysis, and is as follows: Iron oxide (Fe2O3) 30 to 40 mass% Thorium oxide (ThO2) 15 to 25 mass% Magnesium oxide (MgO) 5 to 15 mass %, Aluminum oxide (Al2O3) 4 to 8 mass%, Titanium oxide (TiO2) 3 to 7 mass% It contains 1 to 2 mass% of zirconium oxide (ZrO2: zirconia). Here, the above-mentioned mass % is a relative value when the total of all materials measured as metals or oxides by fluorescent X-ray analysis is taken as 100%.

[0024] The composition of the oil deterioration prevention material 1 according to the embodiment is shown in Table 1 below. Table 1 TIFF2025037286000002.tif51142

[0025] According to the inventor's experiments different from Experimental Examples 1 and 2 described later, when the contained elements were measured as metals or oxides by X-ray fluorescence analysis, if the iron oxide (Fe2O3) content was less than 30 mass%, the effect of suppressing oil deterioration was significantly reduced. It is presumed that this is due to the fact that the amount of negative ions generated was less than the required amount because a crystal structure (fluorite structure, perovskite structure) as a polar material that spontaneously polarizes cannot be formed when the iron (Fe) content is low, and a ferroelectric that is strong enough to polarize naturally is not generated. On the other hand, when the iron oxide (Fe2O3) content was more than 40% by mass when the contained elements were measured as metals or oxides by fluorescent X-ray analysis, the effect of suppressing oil deterioration did not change even if the content was increased beyond that. This is presumably because the high iron content sufficiently forms a crystal structure (fluorite structure, perovskite structure) as a polar material that is spontaneously polarized, and a ferroelectric substance that is sufficiently polarized to cause spontaneous polarization is generated, ensuring the amount of negative ions necessary to suppress oil deterioration. For these reasons, the iron content was determined so that the iron oxide content would be 30 to 40 mass % of the total when the included elements were measured as metals or oxides by fluorescent X-ray analysis.

[0026] According to the inventor's experiments different from Experimental Examples 1 and 2 described below, when the contained elements were measured as metals or oxides by fluorescent X-ray analysis, the performance of inhibiting oil deterioration was reduced when the content of thorium oxide (ThO2) was less than 15 mass%. This is presumably because when the content of thorium oxide is less than 15 mass%, the amount of radiation is reduced, which reduces the amount of negative ions generated. Furthermore, when the contained elements were measured as metals or oxides by fluorescent X-ray analysis, no change was observed in the performance of inhibiting oil deterioration when the thorium oxide content was increased to more than 25 mass%. This is presumably because a sufficient amount of radiation was secured, and a sufficient amount of negative ions necessary for inhibiting oil deterioration were generated. Therefore, the thorium content was determined so that the thorium oxide content, when the included element was measured as a metal or oxide by fluorescent X-ray analysis, was 15 to 25 mass % of the total.

[0027] According to experiments by the inventors different from Experimental Examples 1 and 2 described later, the effect of suppressing oil deterioration was significantly reduced even when the magnesium content was less than 5 mass% magnesium oxide (MgO) when the contained elements were measured as metals or oxides by fluorescent X-ray analysis. It is presumed that this is because, when the magnesium (Mg) content is low, a crystal structure (fluorite structure, perovskite structure) as a polar material that undergoes spontaneous polarization cannot be formed, and a ferroelectric substance that undergoes spontaneous polarization is not generated, resulting in less negative ions than necessary. On the other hand, when the contained elements were measured as metals or oxides by X-ray fluorescence analysis, if the magnesium oxide (MgO) content was more than 15 mass%, the effect of suppressing oil deterioration did not change even if it was increased beyond that. It is presumed that this is because a high magnesium content sufficiently forms a crystal structure (fluorite structure, perovskite structure) as a polar material that is spontaneously polarized, and a sufficient amount of ferroelectric material that is spontaneously polarized is generated, ensuring the amount of negative ions necessary to suppress oil deterioration. For these reasons, the magnesium content was determined so that the magnesium oxide content, when the included elements were measured as metals or oxides by fluorescent X-ray analysis, was 5 to 15 mass % of the total.

[0028] According to experiments by the inventors different from Experimental Examples 1 and 2 described later, when the aluminum content is less than 4 mass% aluminum oxide (Al2O3) when the contained elements are measured as metals or oxides by fluorescent X-ray analysis, the effect of suppressing oil deterioration is significantly reduced. It is presumed that this is because when the aluminum (Al) content is low, it is not possible to form a crystal structure (fluorite structure, perovskite structure) as a polar material that undergoes spontaneous polarization, and a ferroelectric substance that undergoes spontaneous polarization is not generated, resulting in less negative ions than necessary. On the other hand, when the contained elements were measured as metals or oxides by fluorescent X-ray analysis, if the aluminum oxide (Al2O3) content was more than 8 mass%, the effect of suppressing oil deterioration did not change even if it was increased beyond that. It is presumed that this is because the high aluminum content sufficiently forms a crystal structure (fluorite structure, perovskite structure) as a polar material that is spontaneously polarized, and a ferroelectric substance that is sufficiently polarized to ensure the amount of negative ions necessary to suppress oil deterioration. For these reasons, the aluminum content was set so that the aluminum oxide content would be 4 to 8 mass % of the total when the included elements were measured as metals or oxides by fluorescent X-ray analysis.

[0029] According to the inventor's experiments different from Experimental Examples 1 and 2 described later, when the titanium (Ti) content is less than 3 mass% of titanium oxide (TiO2) when the contained elements are measured as metals or oxides by fluorescent X-ray analysis, the effect of suppressing oil deterioration is significantly reduced. As with the other elements mentioned above, it is presumed that this is due to the fact that a crystal structure as a polar material with spontaneous polarization cannot be formed, and a ferroelectric with a degree of spontaneous polarization is not generated. On the other hand, when the titanium (Ti) content is more than 7 mass% when the contained elements are measured as metals or oxides by X-ray fluorescence analysis, the effect of suppressing oil deterioration does not change even if the titanium oxide (TiO2) content is increased beyond 7 mass%. It is presumed that this is because, like the other elements mentioned above, a crystal structure as a polar material with spontaneous polarization is sufficiently formed, a ferroelectric material with a degree of spontaneous polarization is sufficiently generated, and the amount of negative ions necessary to suppress oil deterioration is secured. Therefore, the titanium content was set so that the titanium oxide content would be 3 to 7 mass % of the total when the included elements were measured as metals or oxides by fluorescent X-ray analysis.

[0030] According to the inventor's experiments different from Experimental Examples 1 and 2 described later, when the zirconium (Zr) content is less than 1 mass% of zirconium oxide (ZrO2) when the contained elements are measured as metals or oxides by fluorescent X-ray analysis, the effect of suppressing oil deterioration is significantly reduced. As in the case of the other elements described above, it is presumed that this is due to the fact that a crystal structure as a spontaneously polarized polar material cannot be formed, and a ferroelectric substance with a degree of spontaneous polarization is not generated. On the other hand, when the zirconium (Zr) content is more than 2 mass% zirconium oxide (ZrO2) when the contained elements are measured as metals or oxides by fluorescent X-ray analysis, the effect of suppressing oil deterioration does not change even if the content is increased beyond that. It is presumed that this is because, like the other elements mentioned above, a crystal structure as a spontaneously polarized polar material is sufficiently formed, and the amount of negative ions necessary to suppress oil deterioration is sufficiently secured. Therefore, the zirconium content was set so that the zirconium oxide (ZrO2) content was 1 to 2 mass% of the total when the included elements were measured as metals or oxides by fluorescent X-ray analysis.

[0031] According to another experiment by the inventor different from Experimental Examples 1 and 2 described later, the content of potassium (K) was improved by incorporating 1 to 4 mass% of potassium oxide (KO) when the incorporated element was measured as a metal or oxide by fluorescent X-ray analysis, and the oil deterioration suppression effect was improved when the potassium oxide (KO) was incorporated in an amount of 1 to 4 mass%. When the potassium (K) content is less than 1 mass% when the contained elements are measured as metals or oxides by X-ray fluorescence analysis, it is presumed that a crystal structure as a spontaneously polarized polar material cannot be formed, and a ferroelectric substance with a degree of spontaneous polarization is not generated. On the other hand, when the potassium (K) content was greater than 4 mass% when the contained elements were measured as metals or oxides by X-ray fluorescence analysis, the effect of inhibiting oil deterioration did not change. This is presumably because a sufficient amount of ferroelectric material capable of spontaneous polarization was generated, ensuring the amount of negative ions necessary to inhibit oil deterioration.

[0032] According to experiments by the inventors different from Experimental Examples 1 and 2 described below, it was found that when the above-mentioned oil deterioration prevention material does not contain manganese (Mn), niobium (Nb), calcium (Ca), lead (Pb), phosphorus (P), hafnium (Hf), rubidium (Rb), copper (Cu), or gallium (Ga), the oil deterioration inhibitory effect is reduced compared to when each of these elements is contained. On the other hand, when manganese (Mn), niobium (Nb), calcium (Ca), lead (Pb), phosphorus (P), hafnium (Hf), rubidium (Rb), copper (Cu), and gallium (Ga) are included and added, and the included elements are measured as metals or oxides by fluorescent X-ray analysis, it has been found that when the content of each of manganese oxide (MnO), niobium pentoxide (Nb2O5), calcium oxide (CaO), lead monoxide (PbO), diphosphorus pentoxide (P2O5), hafnium oxide (HfO2), rubidium oxide (Rb2O), copper oxide (CuO), and gallium oxide (Ga2O3) exceeds 1.0 mass%, the oil deterioration inhibitory effect does not change. Therefore, the contents of manganese (Mn), niobium (Nb), calcium (Ca), lead (Pb), phosphorus (P), hafnium (Hf), rubidium (Rb), copper (Cu), and gallium (Ga) were determined so that the contents of manganese oxide, niobium pentoxide, calcium oxide, lead monoxide, diphosphorus pentoxide, hafnium oxide, rubidium oxide, copper oxide, and gallium oxide were 1.0 mass% or less of the total when the included elements were measured as metals or oxides by fluorescent X-ray analysis.

[0033] In the inventor's experiments different from Experimental Examples 1 and 2 described later, when uranium (U) was not contained, the performance of suppressing oil deterioration was lower than when uranium (U) was contained. This is presumably because when uranium (U) is not contained, the amount of radiation is lower and the amount of negative ions generated is reduced. Furthermore, when the content of triuranium octoxide (U3O8) exceeded 1.0 mass% when the contained elements were measured as metals or oxides by fluorescent X-ray analysis, no change was observed in the performance of inhibiting oil deterioration even if the content was increased beyond that. This is presumably because the radiation dose was sufficient, and therefore the negative ions necessary to inhibit oil deterioration were also generated in sufficient quantities. Therefore, the uranium content was determined so that triuranium octoxide (U3O8) would be 1.0 mass% or less when the included elements were measured as metals or oxides by X-ray fluorescence analysis.

[0034] The composition (with manganese and other additives) is shown in Table 2 below. Table 2 TIFF2025037286000003.tif111140

[0035] According to an experiment conducted by the inventor separately, when trace amounts of boron (B) and fluorine (F) were included, the performance of suppressing oil deterioration was significantly improved. It is presumed that this is because when boron (B) and fluorine (F) are included, crystal structures (fluorite structure, perovskite structure) as polar materials that are spontaneously polarized are efficiently formed, increasing the amount of ferroelectrics that are spontaneously polarized, and increasing the amount of negative ions generated. Similarly, in other experiments conducted by the inventors apart from the following experimental examples, the performance of suppressing oil deterioration was improved even in samples containing trace amounts of lithium (Li) and yttrium (Y). It is presumed that this is because, when lithium (Li) and yttrium (Y) are contained, a crystal structure (fluorite structure, perovskite structure) as a polar material that is spontaneously polarized is efficiently formed, the amount of ferroelectrics that are spontaneously polarized increases, and the amount of negative ions generated increases.

[0036] [Experimental Example 1] Here, an experiment conducted by the inventor on the effect of inhibiting oil deterioration will be described. The composition of the oil deterioration prevention material used in Experimental Example 1 contains iron (Fe), thorium (Th), magnesium (Mg), aluminum (Al), titanium (Ti), and zirconium (Zr). The content of each element is measured as a metal or oxide by fluorescent X-ray analysis, and is as follows: Iron oxide (Fe2O3) 35% by mass, Thorium oxide (ThO2) 20% by mass, Magnesium oxide (MgO) 10% by mass, Aluminum oxide (Al2O3) 6% by mass, Titanium oxide (TiO2) 5% by mass, Zirconium oxide (ZrO2: zirconia) 1.5% by mass It includes.

[0037] Such compositions are shown in Table 3 below. Table 3 TIFF2025037286000004.tif51140

[0038] The experimental method and results of Experimental Example 1 conducted by the inventors will be described below. The objective of Experimental Example 1 was to verify the deterioration prevention effect of the oil deterioration prevention material by comparing the change over time in the oil oxidation degree AV value between cases where an oil deterioration prevention material with the composition shown in Table 3 was added to the oil in a fryer and where it was not added. Here, the AV value is a value that increases when oil undergoes hydrolysis due to moisture from fried ingredients or moisture in the air, and is an index used for managing frying oil. The oil deterioration prevention material was sprayed onto a metal plate to be used as a spray plate with a spray thickness of 20 μm and dimensions of 100 x 100 x 3 mm. 1000 ml of commercially available tempura oil was used, and the food ingredient (fried food) was commercially available frozen processed minced meat cutlet. The fryer was a commercially available electric product with a rated capacity of 1L (oil) and a power consumption of 1000W. The tempura thermometer was a commercially available product compatible with 220°C. The oxidation value (AV value) measuring device was a commercially available product (manufactured by Atago Co., Ltd., product name DOM24) that could measure the AV value to 1 / 100.

[0039] The experimental procedures are as follows (1) to (14). (1) Pour 1,000 ml of tempura oil into the fryer. (2) First, as a blank test, carry out the following procedure without adding any oil deterioration prevention material. (3) When the oil temperature is room temperature, measure the oxidation level AV using an oxidation level meter (commercially available DOM24). (4) Electric current is applied to the fryer to heat it up, until it reaches the desired set temperature of 160°C and then maintains that temperature. (5) Add 5 pieces of food (minced cutlets) one after another and fry them. While doing so, add them one by one while trying to maintain the oil temperature at 160℃ as much as possible. (6) Once the frying process is complete, turn off the power immediately. The frying time should be 5 minutes. (7) Repeat the same process every day until the oxidation level measured by the oxidation level meter reaches the target value. (8) When the oxidation level measurement reaches the target value, the work is terminated. The legal limit for the target value is 2.5, but in this experiment, 2.0 was adopted for reasons of safety and the working environment. (9) Every 12 days during the experiment, remove any excess oil that may have accumulated due to filtration and clean the oil tank, and add 150 ml of new oil to make up for any loss in the amount of oil. (10) In the experiment, the oil content of the fried food (how well the oil is cut off), the color of the surface, and the texture will be checked visually. Changes in the color and odor of the tempura oil will also be checked visually. (11) Next, a verification will be conducted on the case where one sprayed plate of oil deterioration prevention material is installed at the bottom of the fryer's oil tank. (12) Clean the fryer and add 1000ml of new oil to the fryer. (13) From here on, repeat steps (3) to (10) to collect comparison data. (14) Cleaning of the oil tank, addition of oil, etc. should be performed at the same time and in the same manner as in the control (blank) test, so that the conditions in both experiments are as similar as possible.

[0040] The results of Experimental Example 1 are explained below. When comparing the visual appearance and texture during frying when the oil deterioration prevention material (sprayed plate) was added, the amount of oil contained in the minced cutlet after frying was clearly less than when the oil deterioration prevention material was not in contact (without the oil deterioration prevention material), and the finished product was crispy. In addition, there was an overwhelmingly less oil smell, and less oil was consumed. These phenomena are thought to be due to the action of the oil deterioration prevention material breaking down the oil molecules into fine particles, allowing the oil to drain easily. The comparison results of the oxidation values ​​(AV values) in Experimental Example 1 are shown in Figure 3. In Figure 3, the vertical axis is the AV value, and the horizontal axis is the number of days of the experiment. The case with the oil deterioration prevention material is shown with a solid line, the case without the oil deterioration prevention material is shown with a dashed line, and the approximate straight lines for each are shown with a dashed line. On the 12th, 23rd, and 36th days of the experiment, cleaning of the oil tank, filtration, and addition of hot water (150 ml) were performed (not shown in Figure 3), and the AV value temporarily improved (the AV value decreased). From the comparison results in Figure 3, it is clear that when oil deterioration prevention material is installed, the oxidation value (AV value) is lower than when oil deterioration prevention material is not installed (no oil deterioration prevention material). It is also clear that the oxidation value (AV value) is less likely to increase even if the number of test days is increased. It is presumed that a reduction reaction occurs when the oil deterioration prevention material is placed in the oil tank and negative ions are supplied to the frying oil in the tank.

[0041] [Experimental Example 2] In Experimental Example 2, an experiment similar to Experimental Example 1 was carried out using an oil deterioration prevention material having a composition different from that used in Experimental Example 1. The oil deterioration prevention material used in Experimental Example 2 contains iron (Fe), thorium (Th), magnesium (Mg), aluminum (Al), titanium (Ti), zirconium (Zr), manganese (Mn), niobium (Nb), uranium (U), calcium (Ca), lead (Pb), phosphorus (P), hafnium (Hf), rubidium (Rb), copper (Cu), and gallium (Ga). The content of each element is measured as a metal or oxide by X-ray fluorescence analysis, and is as follows: Iron oxide (Fe2O3) 35% by mass, Thorium oxide (ThO2) 20% by mass, Magnesium oxide (MgO) 10% by mass, Aluminum oxide (Al2O3) 6% by mass, Titanium oxide (TiO2) 5% by mass, Zirconia (ZrO2) 1.5% by mass, It contains 0.5 mass% each of manganese oxide (MnO), niobium pentoxide (Nb2O5), triuranium octoxide (U3O8), calcium oxide (CaO), lead monoxide (PbO), diphosphorus pentoxide (P2O5), hafnium oxide (HfO2), rubidium oxide (Rb2O), copper oxide (CuO), and gallium oxide (Ga2O3).

[0042] The composition of the oil deterioration prevention material used in Experimental Example 2 is shown in Table 4 below. Table 4 TIFF2025037286000005.tif112142

[0043] The experimental apparatus, experimental procedure, etc. in Experimental Example 2 are the same as those in Experimental Example 1. Although not shown in the chart, the oil deterioration suppression effect was improved in Experimental Example 2 compared to Experimental Example 1. The oxidation value (AV value) was lower than in Experimental Example 1, and the oxidation value (AV value) was less likely to increase over time. This is presumably due to the inclusion of manganese (Mn), niobium (Nb), uranium (U), calcium (Ca), lead (Pb), phosphorus (P), hafnium (Hf), rubidium (Rb), copper (Cu), and gallium (Ga), which increased the amount of negative ions generated.

[0044] The oil deterioration prevention material 1 according to the embodiment acts on the molecules of a fluid containing oil by using ions and other forces, and disperses the large oil molecules that have oxidized and become clumpy. The dispersed (broken) molecules then move around individually, increasing their degree of freedom, reducing the viscosity of the oil and allowing it to remain in a non-sticky (so-called "smooth") state. As a result, it is estimated that the use of the oil deterioration prevention material 1 according to the embodiment improves the drainage of oil from fried foods, prevents highly viscous oil from adhering to the surface of fried foods, and improves the texture of the food. In addition, the oil deterioration prevention material 1 according to the embodiment contains a radioactive substance, and it is presumed that minute amounts of radiation from the substance disperse (break apart) the oil molecules that have deteriorated and become clumpy due to multiple molecules attracting each other, causing them to lose their viscosity, allowing the oil molecules to move around individually and gaining increased freedom of movement. At the same time, it is presumed that negative ions are supplied from the oil deterioration prevention material 1 according to the embodiment (for example, if the oil deterioration prevention material 1 is placed in an oil tank 2, to the oil in the oil tank 2), and the oxidation (deterioration) of the oil is suppressed by the reducing action of the negative ions. Alternatively, the oil deterioration prevention material 1 according to the embodiment contains a material (excitation material) containing a radioactive substance, and by having the above-mentioned composition, forms a crystal structure as a spontaneously polarized polar material. Therefore, it is presumed that radiation from the radioactive substance causes a disturbance in the electric field of the spontaneously polarized crystal particles, generating negative ions. According to the inventor's research, the amount of negative ions generated is, for example, 1000 ions / cm 3 ~10000 pieces / cm 3 The corresponding radiation level is extremely low, about the same as that of a radium hot spring, and does not have any adverse effects on the human body. In addition, according to the oil deterioration prevention material 1 of the embodiment, there is no need to supply power from an external source to suppress the oxidation of oil. Even without external power supply, negative ions continue to act on the oil molecules that have deteriorated and become clumped together due to the attraction of multiple molecules to each other until the excited material stops generating radiation. Furthermore, since the oil deterioration prevention material 1 according to the embodiment is a composition of metal and inorganic substances, it has superior weather resistance, heat resistance, and corrosion resistance compared to materials that contain organic materials such as rubber or resin, and can be used semi-permanently.

[0045] In the first embodiment of the present invention, the oil deterioration prevention material 1 is sintered into a hollow sphere. The composition of the oil deterioration prevention material 1 may be the composition shown in Table 1 or the composition shown in Table 2. 1, as described above, an oil deterioration prevention material 1 according to the embodiment is placed in oil 12 in an oil tank 2 of a fryer 10A (a type of fryer that continuously transfers food materials 11A from an inlet side 13 to an outlet side 17). In the first embodiment, the oil deterioration prevention material 1 is placed in the oil tank 2 as a sintered body 1A. The sintered body 1A is produced by granulating the component powders of the oil deterioration prevention material 1, press-molding the granulated material, and sintering and hardening the granulated material at a desired temperature in an air atmosphere. An example of the oil deterioration prevention material 1 according to the first embodiment is shown in Fig. 4. In Fig. 4, the oil deterioration prevention material 1 has a plurality of sintered bodies 1A formed into a spherical shape, and the plurality of spherical sintered bodies 1A are accommodated in the internal space of a hollow body 3 (e.g., a mesh-like member or a punched metal) having a large number of openings 3A. The hollow body 3 accommodating the plurality of sintered bodies 1A in the internal space is immersed and installed (placed) in the oil tank 2 (see Fig. 1) of a fryer 10A. The oil deterioration prevention material 1 according to the first embodiment shown in Fig. 4 can also be installed in the fryer 10B (a type of fryer that fries food material 11A in a batch manner) described above in Fig. 2. That is, a plurality of spherical sintered bodies 1A are accommodated in the internal space of a hollow body 3 having many openings, and the hollow body 3 accommodating the sintered bodies 1A is immersed and disposed in the oil tank 2 (Fig. 2) of the fryer 10B. Fryers 10A and 10B in which hollow body 3 containing sintered body 1A is placed in oil tank 2 are fryers 10-1 according to the first embodiment.

[0046] Next, a second embodiment of the present invention will be described. In the second embodiment, the oil deterioration prevention material 1 shown in Table 1 or Table 2 above is heated to a melted or semi-molten state, and the melted or semi-molten oil deterioration prevention material 1 is sprayed onto the object to be thermally sprayed (e.g., a metal plate) and collided with the surface layer of the metal plate, so that the oil deterioration prevention material is laminated and adhered to the surface layer of the metal plate. An example of the oil deterioration prevention material 1 according to the second embodiment is shown in Fig. 5. The oil deterioration prevention material 1 is sprayed onto the surface layer of a metal plate 4, which is an object to be sprayed, and then laminated to form a metal plate 1B whose surface layer is covered with the oil deterioration prevention material 1. The metal plate 1B (the oil deterioration prevention material 1 in the second embodiment) is immersed and disposed in the oil tank 2 of the fryer 10. The manner in which the oil deterioration prevention material 1 is sprayed (sprayed) onto the metal plate 4 will be described later with reference to Fig. 6. Metal plate 1B, the surface layer of which is coated with oil deterioration prevention material 1 in the second embodiment, can be immersed and placed in oil tank 2 in both fryer 10A shown in Fig. 1 (a type of fryer that continuously transfers food material 11A from inlet side 13 to outlet side 17) and fryer 10B shown in Fig. 2 (a type of fryer that fries food material 11A in a batchwise manner). In both fryer 10A in Fig. 1 and fryer 10B in Fig. 2, the oil deterioration prevention effect is exhibited. The fryer 10A in FIG. 1 and the fryer 10B in FIG. 2 are fryers 10-2 according to the second embodiment, in which a metal plate 1B having an oil deterioration prevention material 1 laminated on its surface by spraying the oil deterioration prevention material 1 that has been molten or semi-molten, is placed in an oil tank 2.

[0047] As described above, according to fryer 10-1 (a fryer in which spherical sintered body 1A made by sintering oil deterioration prevention material 1 is placed in oil tank 2) and 10-2 (a fryer in which metal plate 1B having a surface layer covered with oil deterioration prevention material 1 is placed in oil tank 2), by placing oil deterioration prevention material 1 (the oil deterioration prevention material according to claim 1 or 2) in oil tank 2, the above-mentioned action effect of oil deterioration prevention material 1 can prevent or suppress oil deterioration. Since it is only necessary to place either the sintered body 1A or the metal plate 1B in the oil tank, there is no restriction on the size of the oil tank 2 of the fryers 10-1, 10-2, and it can be adapted to suit any size. Furthermore, since the oil deterioration prevention material 1 can exert its effect of preventing oil deterioration without supplying electricity from an external source, it can be applied regardless of the presence or absence of a power supply facility as long as there is space to install a fryer, and is highly versatile.

[0048] Thermal spraying in the second embodiment will be described with reference to FIG. "Thermal spraying" is a surface coating process in which the material constituting the coating (the inorganic powder constituting the oil deterioration prevention material 1) is heated and melted or semi-melted by some kind of thermal energy source, and at the same time kinetic energy is imparted to produce droplets 1H (flying droplets) flying at high speed (see FIG. 6(1)), which are sprayed and collided one after another against the substrate surface of the object to be sprayed (the surface of the metal plate 4 in the second embodiment) (see FIG. 6(2)), and are laminated on the surface layer of the metal plate 4 to form a coating (see FIG. 6(3)). That is, the thermal spraying in the second embodiment has the following processes (1) to (3), which are shown diagrammatically in FIG. 6(1) to (3), respectively. (1) Heating and acceleration of the spray material (inorganic powder constituting the oil deterioration prevention material 1) by a heat source. (2) The droplets collide with the substrate (the metal plate 4 in the second embodiment), and are flattened and solidified. (3) Layers of flattened particles.

[0049] In the heating and accelerating process of the spraying material in process (1) shown in Figure 6 (1), the desired coating can be obtained by selecting the spraying parameters (temperature, speed, particle size, melting point, specific heat, thermal conductivity, etc.) that give the optimal temperature and speed to the flying droplet 1H. In Figure 6 (1), the thermal energy and kinetic energy required for the flying droplet 1H are indicated by arrow E. In the process (2) shown in Fig. 6(2), the droplet 1H collides with the substrate, flattens, and solidifies as the high-temperature, high-speed flying droplet 1H collides with the substrate 4 (metal plate 4), releasing kinetic and thermal energy to the substrate 4, and the droplet flattens (arrow F) and solidifies. In Fig. 6(2), the flattened particle on the substrate 4 is indicated by the symbol 1P. Process (3) shown in Figure 6 (3) shows the process of stacking flattened particles 1P. The droplets collide with the substrate 4 and solidify while flattening, and the particles 1P (splats) are stacked one after another and adhere to each other to form a coating. Figure 6 (3) shows the stacked state of the particles 1P (splats), and the metal plate 4 with the particles 1P stacked is the metal plate 1B whose surface layer is coated with the oil deterioration prevention material 1.

[0050] In the second embodiment, a metal plate 1B having a surface layer coated with an oil deterioration prevention material 1 is produced by the method described with reference to FIG. 6. For this purpose, the oil deterioration prevention material 1, which is an inorganic powder, is sprayed in a molten or semi-molten state (close to being molten) onto a base material including a thin plate of metal (material usable in the food industry, such as SUS or aluminum), so that a laminated coating layer (coating) of a desired thickness can be formed on the metal base plate. For this reason, for example, film formation in units of 20 μm is possible. By forming such a thin film (coating in units of 20 μm thick), the deterioration suppression and prevention effect of the oil deterioration prevention material 1 is reliably exerted. In the second embodiment, the oil deterioration prevention material 1 can be sprayed in a molten or semi-molten state (close to being molten). 2 Even when a device that can suppress oil deterioration over a wide area (area) is required, the oil deterioration prevention material 1 can be applied over an area of ​​1 m 2 By coating the surface layer of the metal base material 4 having an area of ​​about 100 nm, the above requirement can be met. Alternatively, since the oil deterioration prevention material 1 can be reliably coated over the desired area of ​​the surface layer of the metal base material 4, multiple metal base materials 1B of the same size coated with the oil deterioration prevention material 1 can be manufactured, and the multiple metal base materials 1B can be aligned and placed in an oil tank, or the oil tank can be filled with metal base materials of the same size coated with the oil deterioration prevention material 1, thereby exerting the oil deterioration inhibitory effect. Furthermore, in the second embodiment, the oil deterioration prevention material 1 can be formed (the oil deterioration prevention material 1 can be formed to the desired size) by spraying it onto a metal plate 4 of a desired size, so it can be installed even in narrow gaps, etc., and there are few restrictions on the installation location. In addition, if the oil deterioration prevention material 1 according to the second embodiment is sprayed onto a metal material that has been processed into a near-net shape in advance, it can be formed into a near-net shape. In other words, it can be formed into any shape. Furthermore, the oil deterioration prevention material 1 according to the second embodiment is sprayed in a nearly molten state, so there is no elution or dust during processing, and it can be used in the food industry, which is sensitive to the inclusion of impurities.

[0051] 7 showing an embodiment of a frying pan to which the present invention is applied, the main body 52 of the frying pan generally designated by reference numeral 50 is made of a metal material such as iron, aluminum, titanium, etc. A cross section of the main body 52 is shown in the region designated by reference numeral S in Fig. 7, and the surface side of the metal material constituting the main body 52 (the surface on the side that comes into contact with food, not shown, and is heated: the upper side in region S in Fig. 7) is coated by thermal spraying with the oil deterioration prevention material 1 described with reference to Figs. 1 to 6, and the surface side of the oil deterioration prevention material 1 is coated with a fluororesin 56 (fluorocarbon resin: for example, tetrafluoroethylene: PTFE). The inventor's experiments have shown that food cooked in the frying pan 50 shown in Fig. 7 has an extremely good texture when coated with the oil deterioration prevention material 1. Furthermore, the inventor's experiments have confirmed that coating the surface side of the oil deterioration prevention material 1 with fluororesin 56 improves both the heat resistance and durability of the frying pan 50 coated with the oil deterioration prevention material 1. In FIG. 7, reference numeral 58 denotes a handle of the frying pan.

[0052] It should be noted that the illustrated embodiment is merely an example and is not intended to limit the technical scope of the present invention. [Explanation of symbols]

[0053] 1...Oil deterioration prevention material 1A···Sintered body 1B: Metal plate with the surface coated with oil deterioration prevention material 2...Oil tank 3...Hollow body 3A...Opening 4...metal plate 10, 10A, 10B, 10-1, 10-2... Flyer

Claims

1. Contains iron, thorium, magnesium, aluminum, titanium, zirconium, When the elements contained therein are measured as metals or oxides by X-ray fluorescence analysis, 30 to 40% by mass of iron oxide, 15 to 25 mass% thorium oxide, 5 to 15% by mass of magnesium oxide, 4 to 8% by mass of aluminum oxide, 3 to 7 mass% titanium oxide, Zirconium oxide 1 to 2 mass% An oil deterioration prevention material comprising:

2. Contains manganese, niobium, uranium, calcium, lead, phosphorus, hafnium, rubidium, tin, copper, and gallium. When the elements contained therein are measured as metals or oxides by X-ray fluorescence analysis, The oil deterioration inhibitor according to claim 1, containing 0 to less than 1.0 mass% of each of manganese oxide, niobium pentoxide, triuranium octoxide, calcium oxide, lead monoxide, diphosphorus pentoxide, hafnium oxide, rubidium oxide, tin oxide, copper oxide, and gallium oxide.

3. 3. A fryer comprising a sintered body of the oil deterioration prevention material according to claim 1 or 2, disposed in an oil tank.

4. The fryer according to claim 3, wherein the sintered body is formed into a spherical shape, the spherical sintered body is disposed in an internal space of a hollow body made of a material having a large number of openings, and the hollow body with the sintered body disposed in the internal space can be immersed in an oil tank.

5. 3. A fryer comprising a metal plate having a surface coated with the oil deterioration prevention material according to claim 1 or 2 by thermal spraying, the metal plate being placed in an oil tank.

6. The oil deterioration prevention material according to claim 1 or 2 is heated to a melted or semi-molten state, The oil deterioration prevention material in a molten or semi-molten state is sprayed onto the object to be thermally sprayed, and is caused to collide with the surface layer of the metal plate; A method for thermal spraying an oil deterioration prevention material, comprising laminating and adhering the oil deterioration prevention material to a surface layer of the metal plate.

7. 3. A frying pan, the surface of which is coated with the oil deterioration prevention material according to claim 1 or 2, and further coated with a fluororesin.

Citation Information

Patent Citations

  • JP1974016623A

  • Oil-circulation fryer, and manufacturing method of deep-fried food

    JP2005296417A